Improving speech perception in noise with current focusing in cochlear implant users - Srinivasan, Arthi G.; Padilla, Monica; Shannon, Robert V.; Landsberger, David M. (Hearing research, 2013)
Cochlear implant (CI) users typically have excellent speech recognition in quiet but struggle with understanding speech in noise. It is thought that broad current spread from stimulating electrodes causes adjacent electrodes to activate overlapping populations of neurons which results in interactions across adjacent channels. Current focusing has been studied as a way to reduce spread of excitation, and therefore, reduce channel interactions. In particular, partial tripolar stimulation has been shown to reduce spread of excitation relative to monopolar stimulation. However, the crucial question is whether this benefit translates to improvements in speech perception. In this study, we compared speech perception in noise with experimental monopolar and partial tripolar speech processing strategies. The two strategies were matched in terms of number of active electrodes, microphone, filterbanks, stimulation rate and loudness (although both strategies used a lower stimulation rate than typical clinical strategies). The results of this study showed a significant improvement in speech perception in noise with partial tripolar stimulation. All subjects benefited from the current focused speech processing strategy. There was a mean improvement in speech recognition threshold of 2.7 dB in a digits in noise task and a mean improvement of 3 dB in a sentences in noise task with partial tripolar stimulation relative to monopolar stimulation. Although the experimental monopolar strategy was worse than the clinical, presumably due to different microphones, frequency allocations and stimulation rates, the experimental partial-tripolar strategy, which had the same changes, showed no acute deficit relative to the clinical. ► Current focusing can improve speech perception in noise. ► All subjects showed a benefit with the current focused strategy. ► Experimental strategies used a long phase duration and low stimulation rate; optimization for clinical use may be beneficial. ► Experimental strategies were tested acutely; chronic testing would be useful.